Pressure‐activated microsyringe (PAM) fabrication of bioactive glass–poly(lactic‐co‐glycolic acid) composite scaffolds for bone tissue regeneration. (29th October 2015) - Mattioli‐Belmonte, M.; De Maria, C.; Vitale‐Brovarone, C.; Baino, F.; Dicarlo, M.; Vozzi, G.
Abstract: The aim of this work was the fabrication and characterization of bioactive glass–poly(lactic‐ co ‐glycolic acid) (PLGA) composite scaffolds mimicking the topological features of cancellous bone. Porous multilayer PLGA–CEL2 composite scaffolds were innovatively produced by a pressure‐activated microsyringe (PAM) method, a CAD/CAM processing technique originally developed at the University of Pisa. In order to select the optimal formulations to be extruded by PAM, CEL2–PLGA composite films (CEL2 is an experimental bioactive SiO2 –P2 O5 –CaO–MgO–Na2 O–K2 O glass developed at Politecnico di Torino) were produced and mechanically tested. The elastic modulus of the films increased from 30 to > 400 MPa, increasing the CEL2 amount (10–50 wt%) in the composite. The mixture containing 20 wt% CEL2 was used to fabricate 2D and 3D bone‐like scaffolds composed by layers with different topologies (square, hexagonal and octagonal pores). It was observed that the increase of complexity of 2D topological structures led to an increment of the elastic modulus from 3 to 9 MPa in the composite porous monolayer. The elastic modulus of 3D multilayer scaffolds was intermediate (about 6.5 MPa) between the values of the monolayers with square and octagonal pores (corresponding to the lowest and highest complexity, respectively). MG63 osteoblast‐like cells and periosteal‐derived precursor cells (PDPCs) were used to assess the biocompatibility of the 3D bone‐like scaffolds. A significant increase in cell proliferation between 48 h and 7 days of culture was observed for both cell phenotypes. Moreover, qRT–PCR analysis evidenced an induction of early genes of osteogenesis in PDPCs. Copyright © 2015 John Wiley & Sons, Ltd.